2006
DOI: 10.1086/508530
|View full text |Cite
|
Sign up to set email alerts
|

A New Cepheid Distance to the Maser‐Host Galaxy NGC 4258 and Its Implications for the Hubble Constant

Abstract: We present initial results from a time-series BVI survey of two fields in NGC 4258 using the Advanced Camera for Surveys onboard the Hubble Space Telescope. This galaxy was selected because of its accurate maser-based distance, which is anticipated to have a total uncertainty of ∼ 3%. The goal of the HST observations is to provide an absolute calibration of the Cepheid Distance Scale and to measure its dependence on chemical abundance (the so-called "metallicity effect").We carried out observations of two fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
452
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(487 citation statements)
references
References 63 publications
32
452
1
2
Order By: Relevance
“…In fact, Cepheids have proved to be extremely useful and robust to determine distances to LMC using as reference direct distance determinations to other galaxies. Macri et al (2006) used the Cepheids in NGC 4258, which has a direct maser-based distance (Herrnstein et al 1999), to determine a distance modulus to LMC that is almost identical to the EB value. It follows that the derived distances using EBs are not only fully compatible among themselves, but also with other direct distance determination methods.…”
Section: The Distance To M 31mentioning
confidence: 99%
“…In fact, Cepheids have proved to be extremely useful and robust to determine distances to LMC using as reference direct distance determinations to other galaxies. Macri et al (2006) used the Cepheids in NGC 4258, which has a direct maser-based distance (Herrnstein et al 1999), to determine a distance modulus to LMC that is almost identical to the EB value. It follows that the derived distances using EBs are not only fully compatible among themselves, but also with other direct distance determination methods.…”
Section: The Distance To M 31mentioning
confidence: 99%
“…Herrnstein et al (1999) obtained the distance of this galaxy by fitting a simple kinematic model to the maser radial velocities and VLBI proper motions (7.3 ± 0.4 Mpc). The Cepheid distance is 7.5 ± 0.3 Mpc (Macri et al 2006). In addition, HST trigonometric parallaxes for a sample of Cepheids have become available (Benedict et al 2007), confirming the Key Project period-luminosity calibration, as shown in Figure 25.…”
Section: Measurement Of the Hubble Constantmentioning
confidence: 88%
“…Here, we describe some of the refinements to the basic model. The distance determined from the accelerations and proper motions of the maser features under the assumption † Present address: 60 Garden Street, MS-42, Cambridge, MA 02138 USA of circular orbits is 7.2 ± 0.5 Mpc ; compare cepheid distance of 7.5 ±0.25 Mpc for an LMC distance of 50 kpc by Macri et al, 2007). At this (maser distance) 1 mas = 0.035 pc = 1.1 × 10 17 cm.…”
Section: Introductionmentioning
confidence: 93%